2003
DOI: 10.1055/s-2003-42342
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders During Pregnancy and Postpartum

Abstract: Approximately 30% of women experience some type of anxiety disorder during their lifetime. Women with these disorders may experience profound changes in their symptoms during pregnancy and the postpartum period. In addition, some evidence exists that anxiety disorders can affect pregnancy outcomes. It is important that physicians understand the course of these disorders during pregnancy and available treatments so they can appropriately counsel women who are or intend to become pregnant. This article reviews t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…No estudo australiano citado anteriormente, foram observadas incidências de fobia, entre 5,7 e 10,6% e de síndrome do pânico, entre 0,5 e 2,7% 3 . Por sua vez, a exata incidência ou prevalência de transtorno obsessivo-compulsivo de início no puerpério não é conhecida, mas aceita-se que a gravidez e o pós-parto sejam fatores importantes desencadeadores do problema 27,28 . Por sua vez, os quadros denominados de transtorno do estresse pós-traumático, desencadeados pelo parto, têm sido mais estudados.…”
Section: Renda Da Mulher (R$unclassified
“…No estudo australiano citado anteriormente, foram observadas incidências de fobia, entre 5,7 e 10,6% e de síndrome do pânico, entre 0,5 e 2,7% 3 . Por sua vez, a exata incidência ou prevalência de transtorno obsessivo-compulsivo de início no puerpério não é conhecida, mas aceita-se que a gravidez e o pós-parto sejam fatores importantes desencadeadores do problema 27,28 . Por sua vez, os quadros denominados de transtorno do estresse pós-traumático, desencadeados pelo parto, têm sido mais estudados.…”
Section: Renda Da Mulher (R$unclassified
“…j Key words pregnancy AE heart rate variability AE depression AE anxiety AE antidepressant Introduction Although pregnancy is thought by many to be ''protective'' in terms of mental health and well-being, recent cohort studies have reported a similar incidence of depression and anxiety during gestation as in the postpartum period [3,29]. Depression, anxiety, as well as stress during pregnancy have been associated with a number of adverse outcomes, including preeclampsia, premature delivery, fetal growth restriction, decreased mental and motor development and difficult infant temperament [26,41,54].…”
mentioning
confidence: 99%
“…maternal depression is diagnosed using the same criteria for major depressive disorder, but may also include specific symptoms such as a preoccupation with infant well-being, disinterest in the infant, fear of being left alone with the infant, or intrusiveness that prevents infant rest (APA 2000). Anxiety affects up to 24% of mothers (Heron et al 2004); it includes panic disorder, obsessive compulsive disorder, post-traumatic stress disorder and generalized anxiety disorder (Levine et al 2003). Psychosis affects approximately 0.1-0.2% of new mothers and is characterized by agitation, hallucinations, mood swings or abnormal perceptions that can lead to suicide and homicide (Brokington et al 2002).…”
Section: Résumémentioning
confidence: 99%